Resin composition and electronic component device
By using a compound containing an oxyalkylene structure in the resin composition, the dispersion of inorganic particles is ensured, the problems of narrow gaping and coagulation are solved, and the sealing effect of the electronic part device is improved.
Patent Information
- Application Number
- CN202380037383.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-20
Smart Images

Figure BDA0005109141910000171
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and an electronic component device. Background Art
[0002] Electronic component devices that use insulating materials called sealing materials to seal the periphery of components such as semiconductor chips or between components and substrates are used in various electronic devices. As sealing materials, resin compositions containing thermosetting resins such as epoxy resins and inorganic particles such as silica are widely used.
[0003] In recent years, as electronic devices have become smaller and more powerful, electronic components have become more precise and integrated. As a result, the gaps between electronic components have become narrower, and existing sealing materials are no longer able to provide sufficient sealing effects.
[0004] As a countermeasure for the narrowing of the gap of electronic component devices, for example, Patent Document 1 describes controlling the particle size of inorganic particles contained in a sealing material.
[0005] Patent Document 1 Japanese Patent Application Publication No. 2021-147453 Summary of the invention
[0006] [Problems to be solved by the invention]
[0007] When the particle size of the inorganic particles contained in the sealing material is reduced, the narrowed space can be filled with the sealing material. However, there is a problem that aggregation is easily caused by the interaction between the inorganic particles and the inorganic particles are not easily dispersed well in the resin composition.
[0008] In view of the above circumstances, an object of the present disclosure is to provide a resin composition having excellent dispersibility of inorganic particles even when the particle size of the inorganic particles is small, and an electronic component device using the resin composition.
[0009] [Technical means to solve the problem]
[0010] Means for solving the above-mentioned problems include the following embodiments.
[0011] <1> A resin composition comprises: a resin component, inorganic particles, and a compound containing an oxyalkylene structure, wherein the maximum particle size of the inorganic particles is less than 5 μm.
[0012] <2> according to <1> The resin composition, wherein the resin component comprises epoxy resin.
[0013] <3> according to <1> or <2> In the resin composition, the compound containing an oxyalkylene structure comprises a silicone compound.
[0014] <4> according to <1> to <3> The resin composition described above is used as a sealing material for electronic component devices.
[0015] <5> An electronic component device, comprising <1> to <4> A component sealed with the resin composition described above.
[0016] [Effects of the Invention]
[0017] According to the present disclosure, a resin composition having excellent dispersibility of inorganic particles even when the particle size of the inorganic particles is small, and an electronic component device using the resin composition can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] none DETAILED DESCRIPTION
[0019] Hereinafter, the form for implementing the present invention is described in detail. Wherein, the present invention is not limited to the following embodiments. In the following embodiments, its constituent parts (including component steps, etc.) are not necessary except for the cases specifically indicated. The same is true for numerical values and their ranges, and the present invention is not limited.
[0020] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.
[0021] In the present disclosure, in a numerical range represented by “to”, numerical values described before and after including “to” are respectively regarded as the minimum value and the maximum value.
[0022] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.
[0023] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the plurality of substances present in the composition.
[0024] In the present disclosure, particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition unless otherwise specified.
[0025] In the present disclosure, the terms solid component, solid, liquid, and liquid refer to properties at normal temperature and pressure (eg, 25° C. and atmospheric pressure) unless otherwise specified.
[0026] <Resin composition>
[0027] The resin composition disclosed herein is a resin composition comprising: a resin component, inorganic particles, and a compound containing an oxyalkylene structure (hereinafter also referred to as an oxyalkylene-containing compound), wherein the maximum particle size of the inorganic particles is 5 μm or less.
[0028] The resin composition having such a structure is excellent in the dispersion stability of the inorganic particles even if the particle size of the inorganic particles is small.
[0029] The reason for this is considered to be that, for example, the oxyalkylene group-containing compound contained in the resin composition functions to compatibilize the interface between the inorganic particles and the surrounding resin component, thereby suppressing aggregation of the inorganic particles due to mutual interaction.
[0030] The type of the resin component contained in the resin composition is not particularly limited, and can be selected according to the application of the resin composition, etc.
[0031] For example, when the resin composition is used as a sealing material for an electronic component device, the resin composition may contain a thermosetting resin and a curing agent as resin components.
[0032] (Thermosetting resin)
[0033] The type of thermosetting resin contained in the resin composition is not particularly limited. Specifically, the thermosetting resin includes epoxy resins, phenol resins, urea resins, melamine resins, urethane resins, silicone resins (excluding silicone resins corresponding to compounds containing oxyalkylene groups), unsaturated polyester resins, and the like. In the present disclosure, resins that exhibit both thermoplasticity and thermosetting properties, such as epoxy-containing acrylic resins, are included in the "thermosetting resin". The thermosetting resin may be solid or liquid, preferably solid. The thermosetting resin may be used alone or in combination of two or more.
[0034] The thermosetting resin preferably includes an epoxy resin. Specific examples of the epoxy resin include: a phenol compound selected from phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and the like; αNovolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of naphthol compounds such as -naphthol, β-naphthol, and dihydroxynaphthalene with aliphatic aldehyde compounds such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; triphenylmethane-type epoxy resins obtained by condensing or co-condensing the phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst to obtain a triphenylmethane-type phenol resin, and then epoxidizing the triphenylmethane-type phenol resin; co-condensing the phenolic compounds and naphthol compounds with aldehyde compounds under an acidic catalyst to obtain a triphenylmethane-type phenol resin; A copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by combining a novolac resin and obtaining the novolac resin; a diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; a biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; a distyrene epoxy resin as a diglycidyl ether of a distyrene phenol compound; a sulfur-containing epoxy resin as a diglycidyl ether of bisphenol S, etc.; an epoxy resin as a glycidyl ether of an alcohol such as butanediol, polyethylene glycol, and polypropylene glycol; a glycidyl ester epoxy resin as a glycidyl ester of a polycarboxylic acid compound such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; Glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of isocyanuric acid with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in the molecule; p-xylene-modified epoxy resins as glycidyl ethers of p-xylene-modified phenol resins; m-xylene-modified epoxy resins as glycidyl ethers of m-xylene-modified phenol resins; terpene-modified epoxy resins as Terpene-modified epoxy resin of glycidyl ether of phenol resin; dicyclopentadiene-modified epoxy resin as glycidyl ether of dicyclopentadiene-modified phenol resin; cyclopentadiene-modified epoxy resin as glycidyl ether of cyclopentadiene-modified phenol resin; polycyclic aromatic ring-modified epoxy resin as glycidyl ether of polycyclic aromatic ring-modified phenol resin; naphthalene-type epoxy resin as glycidyl ether of phenol resin containing naphthalene ring; halogenated phenol novolac-type epoxy resin; hydroquinone-type epoxy resin; trimethylolpropane-type epoxy resin; linear aliphatic epoxy resin obtained by oxidizing olefin bonds with peracids such as peracetic acid; aralkyl-type epoxy resin obtained by epoxidizing aralkyl-type phenol resins such as phenol aralkyl resins, naphthol aralkyl resins, etc. The epoxy resins may be used alone or in combination of two or more.
[0035] When the thermosetting resin is an epoxy resin, the epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited. From the perspective of balancing various properties such as formability, reflow resistance, and electrical reliability, it is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq. The epoxy equivalent of the epoxy resin is set to a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.
[0036] When the thermosetting resin is solid at 25°C, the melting point or softening point of the thermosetting resin is not particularly limited. From the viewpoint of blocking resistance, the melting point or softening point of the thermosetting resin is preferably 40°C or higher, more preferably 50°C or higher. From the viewpoint of suppressing the thickening of the resin composition caused by kneading, the melting point or softening point of the thermosetting resin is preferably 150°C or lower, more preferably 140°C or lower, and further preferably 130°C or lower.
[0037] From the viewpoints of strength, fluidity, heat resistance, formability, etc., the content of the thermosetting resin is preferably 0.5% to 50% by mass, more preferably 2% to 30% by mass, and even more preferably 2% to 20% by mass relative to the total mass of the resin composition.
[0038] (Hardener)
[0039] The resin composition may contain a hardener used in combination with a thermosetting resin. Examples of hardeners used in combination with epoxy resins include phenol hardeners, amine hardeners, acid anhydride hardeners, polythiol hardeners, polyaminoamide hardeners, isocyanate hardeners, and blocked isocyanate hardeners. One hardener may be used alone or in combination of two or more. From the viewpoint of improving heat resistance, the hardener is preferably a phenol hardener (a hardener containing a phenolic hydroxyl group as a functional group that reacts with an epoxy group). The hardener may be solid or liquid at normal temperature and pressure (e.g., 25° C., atmospheric pressure), preferably solid.
[0040] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, substituted or unsubstituted biphenols, and the like; phenol compounds selected from phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and the like; αNovolac-type phenolic resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of naphthol compounds such as -naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde under an acidic catalyst; aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins synthesized from the phenolic compounds and dimethoxy-p-xylene, bis(methoxymethyl)biphenyl, etc.; p-xylene and / or m-xylene-modified phenolic resins; tri- Melamine modified phenol resin; terpene modified phenol resin; dicyclopentadiene type phenol resin and dicyclopentadiene type naphthol resin synthesized by copolymerization of the phenolic compound and dicyclopentadiene; cyclopentadiene modified phenol resin; polycyclic aromatic ring modified phenol resin; biphenyl type phenol resin; triphenylmethane type phenol resin obtained by condensing or co-condensing the phenolic compound with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resin obtained by copolymerizing two or more of these, etc. The phenol hardener may be used alone or in combination of two or more.
[0041] The functional group equivalent of the hardener (hydroxyl equivalent in the case of a phenol hardener, active hydrogen equivalent in the case of an amine hardener) is not particularly limited. From the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability, the functional group equivalent of the hardener is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq.
[0042] The hydroxyl equivalent in the case of a phenol curing agent is a value calculated based on the hydroxyl value measured in accordance with JIS K0070: 1992. In addition, the active hydrogen equivalent in the case of an amine curing agent is a value calculated based on the amine value measured in accordance with JIS K7237:1995.
[0043] When the curing agent is solid, its softening point or melting point is not particularly limited. For example, from the viewpoint of moldability and reflow resistance when the resin composition is used as a sealing material, the softening point or melting point of the curing agent is preferably 40°C to 180°C, and from the viewpoint of operability during the production of the resin composition, it is more preferably 50°C to 130°C.
[0044] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.
[0045] The equivalent ratio of the thermosetting resin to the hardener, that is, the ratio of the number of functional groups in the hardener to the number of functional groups in the thermosetting resin (the number of functional groups in the hardener / the number of functional groups in the thermosetting resin) is not particularly limited. From the perspective of suppressing the unreacted components of each, the equivalent ratio of the thermosetting resin to the hardener is preferably set in the range of 0.5 to 2.0, and more preferably in the range of 0.6 to 1.3. From the perspective of formability, the equivalent ratio of the thermosetting resin to the hardener is further preferably set in the range of 0.8 to 1.2.
[0046] (Inorganic particles)
[0047] The material of the inorganic particles contained in the resin composition is not particularly limited. As the material of the inorganic particles, specifically, the inorganic materials such as silicon dioxide such as fused silica and crystalline silica, glass, aluminum oxide, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, magnesium oxide, silicon carbide, beryllium oxide, zirconium oxide, zircon, forsterite, steatite, spinel, mullite, titanium dioxide, talc, clay, mica can be listed. The inorganic particles with flame retardant effect can also be used. As the inorganic particles with flame retardant effect, the composite metal hydroxides such as aluminum hydroxide, magnesium hydroxide, magnesium and zinc composite hydroxides, zinc borate, etc. can be listed. In the inorganic particles, with respect to the viewpoint of reducing the linear expansion coefficient, the silicon dioxide such as fused silica is preferably used, and with respect to the viewpoint of high thermal conductivity, aluminum oxide is preferably used.
[0048] The inorganic particles contained in the resin composition may be only one kind or two or more kinds.
[0049] In the present disclosure, the maximum particle size of the inorganic particles contained in the resin composition is 5.0 μm or less. The maximum particle size of the inorganic particles contained in the resin composition may be less than 5.0 μm, 4.5 μm or less, 4.0 μm or less, or 3.5 μm or less.
[0050] The volume average particle size of the inorganic particles is not particularly limited. From the viewpoint of coping with narrowing of gaps in electronic component devices, the volume average particle size of the inorganic particles is preferably 4.0 μm or less, more preferably 3.5 μm or less, and even more preferably 3.0 μm or less.
[0051] From the viewpoint of suppressing aggregation of the inorganic particles, the volume average particle size of the inorganic particles is preferably 0.1 μm or more, more preferably 0.2 μm or more, and still more preferably 0.3 μm or more.
[0052] The volume average particle size of the inorganic particles can be measured as a particle size (D50) at which the accumulation from the smaller diameter side is 50% in a volume-based particle size distribution measured by a laser scattering diffraction particle size distribution analyzer.
[0053] The specific surface area of the inorganic particles obtained by the Brunauer Emmett Teller (BET) method is not particularly limited. From the perspective of narrowing the gap of electronic component devices, the specific surface area of the inorganic particles obtained by the BET method is preferably 0.1 m2 / g or more, more preferably 0.5 m2 / g or more, and further preferably 1.0 m2 / g or more.
[0054] From the viewpoint of suppressing aggregation of inorganic particles, the specific surface area of the inorganic particles as determined by the BET method is preferably 50 m 2 / g or less, more preferably 20 m 2 / g or less, and still more preferably 10 m 2 / g or less.
[0055] The specific surface area of the inorganic particles by the BET method can be measured based on the nitrogen adsorption capacity of the inorganic particles in accordance with JIS Z 8830:2013.
[0056] The specific surface area of the inorganic particles obtained by image analysis is not particularly limited. From the perspective of narrowing the gap of electronic component devices, the specific surface area of the inorganic particles obtained by image analysis is preferably 0.1 m2 / g or more, more preferably 0.5 m2 / g or more, and further preferably 1.0 m2 / g or more.
[0057] From the viewpoint of suppressing aggregation of inorganic particles, the specific surface area of the inorganic particles obtained by image analysis is preferably 50 m 2 / g or less, more preferably 20 m 2 / g or less, and further preferably 10 m 2 / g or less.
[0058] The specific surface area of the inorganic particles obtained by the image analysis method can be calculated by taking an image of the inorganic particles using an electron microscope or the like and assuming that the particles in the obtained image are spherical.
[0059] The shape of the inorganic particles is not particularly limited, but is preferably spherical in terms of filling properties and mold abrasion resistance.
[0060] The content of inorganic particles is not particularly limited. From the perspective of further improving the thermal expansion coefficient, thermal conductivity, elastic coefficient and other properties of the cured product of the resin composition, the content of inorganic particles is preferably more than 30% by volume of the entire resin composition, more preferably more than 40% by volume, and further preferably more than 50% by volume, particularly preferably more than 60% by volume, and extremely preferably more than 70% by volume. From the perspective of improving the fluidity of the resin composition, reducing the viscosity, etc., the content of inorganic particles is preferably less than 99% by volume of the entire resin composition, more preferably less than 98% by volume, and further preferably less than 97% by volume.
[0061] In addition, for example, when the resin composition is used for compression molding, the content of the inorganic particles can be set to 70 volume % to 99 volume % of the entire resin composition, or it can be set to 80 volume % to 99 volume %, or it can be set to 83 volume % to 99 volume %, or it can be set to 85 volume % to 99 volume %.
[0062] The content of inorganic particles in the cured product of the resin composition can be measured as follows. First, the total mass of the cured product is measured, and the cured product is calcined at 400°C for 2 hours and then at 700°C for 3 hours to evaporate the resin components and the like, and the mass of the remaining inorganic particles is measured. The volume is calculated from the obtained masses and their respective specific gravities, and the ratio of the volume of the inorganic particles to the total volume of the cured product is obtained as the content of the inorganic particles.
[0063] (Oxyalkylene-containing compound)
[0064] In the present disclosure, the oxyalkylene-containing compound refers to a compound containing an oxyalkylene structure in the molecule. The oxyalkylene structure refers to -[OC m H 2m ] n - represents a molecular structure. n in the formula may be 1 or a number greater than 2 (i.e., polyalkylene oxide). m in the formula may be 2 (ethylene), 3 (propylene), or a number greater than 2, or a combination of structural units having different m. From the viewpoint of the dispersibility of the inorganic particles, m is preferably 2 or 3.
[0065] The type of the oxyalkylene-containing compound contained in the resin composition is not particularly limited. For example, silicone resins such as silicone compounds, acrylic resins, ester resins, fluororesins, etc. can be cited. From the perspective of obtaining the effect of a stress relaxant for the resin composition, the oxyalkylene-containing compound is preferably a silicone compound. In the present disclosure, the so-called silicone compound refers to a compound having a main chain containing a siloxane bond.
[0066] The resin composition may contain only one type of oxyalkylene-containing compound, or may contain two or more types.
[0067] The oxyalkylene-containing compound may also contain functional groups other than the oxyalkylene structure. When the oxyalkylene-containing compound contains functional groups other than the oxyalkylene structure, for example, the functional groups can be inhibited from reacting with the resin component or inorganic particles in the resin composition to cause components to ooze out of the cured product. Specifically, the functional groups other than the oxyalkylene structure include epoxy, amino, mercapto, vinyl, acrylic, methacrylic, isocyanate, anhydride, and aralkyl groups. Among these, epoxy and amino groups are preferred, and epoxy groups are more preferred.
[0068] The oxyalkylene group-containing compound may contain only one type of functional group other than the oxyalkylene structure, or may contain two or more types.
[0069] In one embodiment, the oxyalkylene-containing compound may be a silicone compound having an oxyalkylene structure in a side chain, or may be a silicone compound having an oxyalkylene structure in a side chain and having a functional group other than the oxyalkylene structure in at least one of the side chain or the main chain terminal.
[0070] The molecular weight of the oxyalkylene-containing compound is not particularly limited. For example, it can be selected from the range of 200 to 10,000. The oxyalkylene-containing compound may be in a liquid or solid state before being mixed with other raw materials. From the perspective of ease of mixing with the thermosetting resin and the inorganic particles, a liquid is preferred.
[0071] The content of the oxyalkylene-containing compound in the resin composition is not particularly limited. From the viewpoint of dispersibility of the inorganic particles, the content of the oxyalkylene-containing compound is preferably 0.2% by mass or more, more preferably 0.7% by mass or more, and further preferably 1.0% by mass or more relative to the total mass of the resin composition.
[0072] From the viewpoint of suppressing a decrease in strength of the resin composition during curing, the content of the oxyalkylene group-containing compound is preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and still more preferably 2.0 mass % or less, based on the total mass of the resin composition.
[0073] The content of the oxyalkylene-containing compound in the resin composition is not particularly limited. From the viewpoint of dispersibility of the inorganic particles, the content of the oxyalkylene-containing compound is preferably 0.2 parts by mass or more, more preferably 0.7 parts by mass or more, and further preferably 1.0 parts by mass or more relative to 100 parts by mass of the inorganic particles.
[0074] From the viewpoint of suppressing a decrease in strength of the resin composition during curing, the content of the oxyalkylene group-containing compound is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and still more preferably 2.0 parts by mass or less, based on 100 parts by mass of the inorganic particles.
[0075] (hardening accelerator)
[0076] The resin composition may also contain a hardening accelerator. Specific examples of the hardening accelerator include: diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; and phenol novolacs of the cyclic amidine compounds or their derivatives. Lacquer salts; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluenequinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds with π bonds such as diazonium methane, etc. to these compounds; cyclic amidinium compounds such as tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, and tetraphenylborate of N-methylmorpholine; pyridine, triethylamine, triethylenediamine, benzyldimethylamine , triethanolamine, dimethylaminoethanol, tris(dimethylaminomethyl)phenol and other tertiary amine compounds; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl(p-toluene)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkylalkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine, tri(trialkoxyphenyl)phosphine , tri(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tri(benzyl)phosphine and other tertiary phosphine and other organic phosphine; phosphine compounds such as complexes of the organic phosphine and organic boron; compounds with intramolecular polarization formed by adding the organic phosphine or the phosphine compound to maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone and other quinone compounds, compounds with π bonds such as diazonophenylmethane and the like;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1 -Bromo-2-naphthol, 6-bromo-2-naphthol, 4-bromo-4′-hydroxybiphenyl and other halogenated phenol compounds reacted and then dehydrohalogenated to obtain a compound with intramolecular polarization; tetraphenyl phosphonium and other tetraphenyl phosphonium, tetraphenyl phosphonium tetra-p-toluene borate and other tetraphenyl borate of tetrasubstituted phosphonium; tetrasubstituted phosphonium compounds such as salts of tetrasubstituted phosphonium and phenol compounds; phosphate betaine compounds; adducts of phosphonium compounds and silane compounds, etc. The hardening accelerator can be used alone or in combination of two or more. ;
[0077] When an epoxy resin is used as the thermosetting resin, particularly preferred curing accelerators include triphenylphosphine and an adduct of triphenylphosphine and a quinone compound.
[0078] The content of the hardening accelerator is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the resin component. If the amount of the hardening accelerator is 0.1 parts by mass or more relative to 100 parts by mass of the resin component, there is a tendency to cure well in a short time. If the amount of the hardening accelerator is 30 parts by mass or less relative to 100 parts by mass of the resin component, there is a tendency to obtain a good molded product without too fast a hardening speed.
[0079] (additive)
[0080] In addition to the above components, the resin composition may contain various additives such as coupling agents, ion exchangers, release agents, flame retardants, colorants, stress relaxants, etc. In addition to the additives exemplified below, the resin composition may contain various additives commonly used in the art as needed.
[0081] (Coupling agent)
[0082] The resin composition may contain a coupling agent to improve the adhesion between the resin component and the inorganic particles. Examples of the coupling agent include known coupling agents such as silane compounds, titanium compounds, aluminum chelate compounds, and aluminum / zirconium compounds.
[0083] Examples of the silane compound include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-ureidopropyltriethoxysilane, octenyltrimethoxysilane, glycidoxyoctyltrimethoxysilane, and methacryloxyoctyltrimethoxysilane.
[0084] Examples of the titanium compound include isopropyl triisostearoyl titanate, isopropyl tri(dioctyl pyrophosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(di-tridecyl phosphite) titanate, tetrakis(2,2-diallyloxymethyl-1-butyl)bis(di-tridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl titanate, isopropyl dimethacrylate isostearyl titanate, isopropyl tri-dodecylbenzenesulfonyl titanate, isopropyl isostearyl diacrylate titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumylphenyl titanate, and tetraisopropyl bis(dioctyl phosphate) titanate.
[0085] When the resin composition contains a coupling agent, the amount of the coupling agent is preferably 0.05 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, based on 100 parts by mass of the inorganic particles.
[0086] (Ion Exchanger)
[0087] The resin composition may also contain an ion exchanger. In particular, when the resin composition is used as a molding material for sealing, it is preferred to contain an ion exchanger from the viewpoint of improving the moisture resistance and high temperature storage characteristics of the electronic component device including the sealed element. There is no particular limitation on the ion exchanger, and existing known ion exchangers can be used. Specifically, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchanger can be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.
[0088] Mg (1-X) Al X (OH)2(CO3) X / 2·mH2O······(A)
[0089] (0 < X ≤ 0.5, m is a positive number)
[0090] When the resin composition contains an ion exchanger, its amount is not particularly limited as long as it is sufficient to capture ions such as halogen ions. For example, the amount of the ion exchanger is preferably 0.1 part by mass to 30 parts by mass, more preferably 1 part by mass to 10 parts by mass, based on 100 parts by mass of the resin component.
[0091] (Release agent)
[0092] From the viewpoint of obtaining good mold release property during molding, the resin composition may also contain a release agent. The release agent is not particularly limited, and known release agents can be used. Specifically, examples include: palm wax, montanic acid, higher fatty acids such as stearic acid, metal salts of higher fatty acids, ester waxes such as montanic acid esters, polyolefin waxes such as polyethylene oxide and non-oxidized polyethylene, etc. The release agent can be used alone or in combination of two or more.
[0093] When the resin composition contains a release agent, its amount is preferably 0.01 part by mass to 10 parts by mass, more preferably 0.1 part by mass to 5 parts by mass, based on 100 parts by mass of the resin component. If the amount of the release agent is 0.01 part by mass or more based on 100 parts by mass of the resin component, there is a tendency to sufficiently obtain mold release property. If it is 10 parts by mass or less, there is a tendency to obtain better adhesion and hardening property.
[0094] (Flame retardant)
[0095] The resin composition may also contain a flame retardant. The flame retardant is not particularly limited, and known flame retardants can be used. Specifically, examples include organic compounds or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms or phosphorus atoms, metal hydroxides, etc. The flame retardant can be used alone or in combination of two or more.
[0096] When the resin composition contains a flame retardant, its amount is not particularly limited as long as it is sufficient to obtain the required flame retardant effect. For example, it is preferably 1 part by mass to 30 parts by mass, more preferably 2 parts by mass to 20 parts by mass, based on 100 parts by mass of the resin component.
[0097] (Colorant)
[0098] The resin composition may also contain a colorant. As the colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, iron oxide, etc. can be cited. The content of the colorant can be appropriately selected according to the purpose, etc. The colorant can be used alone or in combination of two or more.
[0099] When the resin composition contains a colorant, the amount thereof is not particularly limited as long as it is a sufficient amount to obtain the desired coloring effect. For example, the amount of the colorant is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the resin component.
[0100] (Stress Relaxant)
[0101] The resin composition may also contain a stress relaxant. By containing a stress relaxant, the warping deformation of the package and the generation of package cracks when the resin composition is used in the sealing material application can be reduced. As a stress relaxant, commonly used known stress relaxants (flexible agents) can be listed. Specifically, thermoplastic elastomers such as silicone, styrene, olefin, urethane, polyester, polyether, polyamide, and polybutadiene can be listed; rubber particles such as natural rubber (natural rubber, NR), acrylonitrile butadiene rubber (acrylonitrile butadiene rubber, NBR), acrylic rubber, urethane rubber, silicone powder, etc.; methyl methacrylate-styrene-butadiene copolymer (methacrylate methyl styrene butadiene, MBS), methyl methacrylate-silicone copolymer, methyl methacrylate-butyl acrylate copolymer, etc. have a core-shell structure. The stress relaxant can be used alone or in combination of two or more.
[0102] As the oxyalkylene group-containing compound contained in the resin composition, a compound that also functions as a stress relaxant (such as a silicone compound) may be used.
[0103] When the resin composition contains a stress relaxant, the amount thereof (excluding the amount of the oxyalkylene-containing compound) is not particularly limited as long as it is a sufficient amount to obtain the desired stress relaxation effect. For example, the amount of the stress relaxant is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the resin component.
[0104] The resin composition may be solid or liquid at normal temperature and pressure (eg, 25° C., atmospheric pressure), but is preferably solid. The shape of the resin composition when solid is not particularly limited, and examples thereof include powder, granules, and flakes.
[0105] The resin composition produced by the method disclosed herein can be used in various applications. A preferred application of the resin composition is a sealing material for electronic component devices.
[0106] <Electronic Components Device>
[0107] The electronic component device of the present disclosure is an electronic component device including an element sealed with the resin composition of the present disclosure.
[0108] Specifically, the electronic component device includes a supporting member, an element mounted on the supporting member, and a sealing material for sealing the periphery of the element.
[0109] Examples of the indicator member include support members such as a lead frame, a wired conveyor tape, a wiring board, glass, a silicon wafer, and an organic substrate.
[0110] Examples of the element include active elements such as semiconductor chips, transistors, diodes, and thyristors, and passive elements such as capacitors, resistors, and coils.
[0111] The method for sealing the electronic component device using the resin composition is not particularly limited, and can be selected from known methods, such as low pressure transfer molding, injection molding, and compression molding.
[0112] <Method for producing resin composition>
[0113] The method for producing the resin composition is not particularly limited, and the resin composition can be produced by a known method.
[0114] From the viewpoint of workability when the inorganic particles are mixed with other raw materials, the resin composition may be produced by a method in which granules containing the inorganic particles and the resin component are prepared and the granules are mixed with other raw materials.
[0115] In the present disclosure, the “granulated material containing inorganic particles and a resin component” refers to a material containing at least inorganic particles and a resin component in a granulated form.
[0116] The resin component used for preparing the granulated material may be the whole of the resin component contained in the resin composition or may be a part of it.
[0117] For example, in the case where the resin composition contains a thermosetting resin and a hardener as resin components, granules containing inorganic particles and a thermosetting resin, and granules containing inorganic particles and a hardener can be prepared separately. As the granules containing inorganic particles and resin components, only any one of the granules containing inorganic particles and a thermosetting resin and the granules containing inorganic particles and a hardener can be prepared.
[0118] The granulated material containing inorganic particles and a resin component may contain components other than the inorganic particles and the resin component. For example, the granulated material may contain an oxyalkylene group-containing compound.
[0119] From the viewpoint of suppressing the aggregation of inorganic particles, the resin component used in the preparation of the granulated material preferably has a charge opposite to that of the inorganic particles. For example, when the surface of the inorganic particles is positively charged, it is preferred to use a resin component having an anionic functional group such as a phenolic hydroxyl group, and when the surface of the inorganic particles is negatively charged, it is preferred to use a resin component having a cationic functional group such as an amino group.
[0120] The particle size of the granulated material is not particularly limited, and can be selected in consideration of workability when mixed with other materials.
[0121] The particle size of the granulated material can be selected from the range of, for example, 10 μm to 10000 μm, preferably 100 μm to 5000 μm, and more preferably 500 μm to 3000 μm.
[0122] The particle shape of the granulated material is not particularly limited, and may be spherical, columnar, flaky, or needle-shaped.
[0123] The method of preparing granules comprising inorganic particles and resin components and mixing the granules with other raw materials is particularly preferred when using a kneading extruder to manufacture a resin composition. In the case of inorganic particles that are not in a state of granules being dropped from the feeder of the kneading extruder, if the particle diameter of the inorganic particles is too small, it is easy to become the cause of the efficiency decline, poor kneading, etc. of the kneading operation. In the method, the inorganic particles are put into the kneading extruder after being made into the state of granules in advance. Therefore, even in the case of the particle diameter of the inorganic particles being extremely small (that is, the maximum particle diameter is less than 5 μm), a kneading extruder can also be used to efficiently manufacture a uniform resin composition.
[0124] [Example]
[0125] Hereinafter, the embodiments will be described in detail by way of examples, but the present disclosure is not limited to these examples.
[0126] (1) Preparation of granules
[0127] The materials (parts by mass) shown in Table 1 were placed in a 3 L separable flask, and a stirring blade was inserted, followed by stirring at 200 rpm (revolutions / minute) for 2 hours to obtain a varnish-like mixture.
[0128] Then, vacuum drying was performed at 140° C. for 2 hours to remove the solvent until the residual solvent ratio of the mixture was less than 1% by mass, thereby obtaining a solid material. The obtained solid material was pulverized to prepare granules (MB) having a particle size of 1000 μm.
[0129] The obtained granules (2.5 g) were mixed with acetone (20 g), and the resin component in the granules was dissolved by acetone. Then, the mixture was filtered using a filter with a mesh size of 20 μm, and the filtrate was washed with acetone and dried to obtain a residue. The residue rate was calculated by the following formula. The results are shown in Table 1.
[0130] Residue rate (%) = (mass of residue A / mass of granulated material B) × 100
[0131] (2) Preparation of resin composition
[0132] The materials (parts by mass) shown in Table 1 were charged into an extrusion kneading machine to obtain a kneaded product. The obtained kneaded product was pulverized to obtain a resin composition having a particle size of 1000 μm.
[0133] The obtained resin composition (2.5 g) was mixed with acetone (20 g), and the resin component in the resin composition was dissolved by acetone. Then, the mixture was filtered using a filter with a mesh size of 20 μm, and the filtrate was washed with acetone and dried to obtain a residue. The residue rate was calculated by the following formula. The results are shown in Table 1.
[0134] Residue rate (%) = (mass A of residue / mass B of resin composition) × 100
[0135] (3) Evaluation of physical properties of resin composition
[0136] The spiral flow (SF), gel time (GT), storage modulus of elasticity, glass transition temperature (Tg), and molding shrinkage were measured using the resin composition by the following methods.
[0137] (Spiral Flow)
[0138] The resin composition was molded using a spiral flow measurement mold in accordance with EMMI-1-66 at a mold temperature of 175° C., a molding pressure of 6.9 MPa, and a curing time of 120 seconds, and the flow distance (cm) at this time was measured as the spiral flow.
[0139] The spiral flow of the resin composition is preferably 80 cm or more, more preferably 90 cm or more, and further preferably 100 cm or more. The upper limit of the spiral flow is not particularly limited, and an example thereof is 200 cm.
[0140] (Gel time)
[0141] 0.5 g of a sample of the resin composition was placed on a hot plate heated to 175°C, and the sample was unfolded into a 2.0 cm to 2.5 cm circle using a clamp at a rotation speed of 20 to 25 rpm. The time (seconds) from the time the sample was placed on the hot plate until the stickiness of the sample disappeared and the sample became a gel state and was peeled off the hot plate was measured as the gel time.
[0142] The gel time of the resin composition at 175° C. is preferably 30 to 90 seconds, more preferably 40 to 60 seconds.
[0143] (Storage elastic coefficient)
[0144] Using the resin composition, a sheet with a thickness of 0.8 mm was formed under the conditions of a mold temperature of 175°C, a molding pressure of 7 MPa, and a curing time of 90 seconds. A 4 mm × 25 mm plate was cut out from the sheet to make a test piece. The test piece was placed in a solid viscoelasticity measuring device (e.g., manufactured by TA Instruments, model RSA-G2), and a dynamic viscoelasticity measurement based on a three-point bending mode was performed. The measurement conditions were set to a temperature range of 10°C to 40°C, a heating rate of 5°C / min, a vibration frequency of 10 Hz, a strain of 0.2%, and an environment of nitrogen flow. The storage elastic coefficient E′ (GPa) at a temperature of 25°C is shown in Table 2.
[0145] (Glass transition temperature)
[0146] The linear expansion coefficient of the cured product of the resin composition at 40°C to 240°C was measured, and the temperature of the intersection of the tangent line at 40°C to 80°C and the tangent line at 200°C to 240°C obtained by the measurement was defined as the glass transition temperature (°C) of the cured product.
[0147] The linear expansion coefficient of the hardened material is measured by thermomechanical analysis (TMA: Thermal Mechanical Analysis) based on JIS K 7197: 2012. Specifically, the slope of the tangent line at 40°C to 240°C when the strain of the hardened material is plotted against the temperature is used as the linear expansion coefficient. The test load is set to 5g and the heating rate is set to 5°C / min. As a thermomechanical analysis device, TMA4000SE of Netzsch is used.
[0148] The test piece used for the determination of the linear expansion coefficient was produced by molding the resin composition using a transfer molding machine under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds, followed by post-curing at 175°C for 5 hours. The shape of the test piece was set to a rectangular parallelepiped of 4 mm × 4 mm × 20 mm.
[0149] (Molding shrinkage)
[0150] The resin composition was molded using a transfer molding machine at a molding temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds to obtain a plate-shaped molded product (127 mm in length, 12.7 mm in width, and 6.4 mm in thickness). The molding shrinkage (%) was calculated using the following formula based on the length D of the mold cavity at 25°C and the length d of the molded product at room temperature (25°C) measured in advance.
[0151] Molding shrinkage (%) = ((Dd) / D) × 100
[0152] [Table 1]
[0153] MB1 MB2 MB3 MB5 MB9 MB13 MB14 MB24 MB25 MB28 MB29 MB30 Epoxy resin 1 100 100 100 100 100 100 100 Epoxy Resin 2 100 Epoxy Resin 3 100 Hardener 1 100 Hardener 2 100 Hardener 3 100 Inorganic particles 1 817.1 891.4 965.7 817.1 817.1 817.1 817.1 817.1 742.9 742.9 742.9 742.9 Inorganic particles 2 238.3 260.0 281.7 238.3 238.3 238.3 238.3 238.3 216.7 216.7 216.7 216.7 Coupling agent 5.7 6.2 6.8 5.7 5.7 5.7 5.7 5.7 5.2 5.2 5.2 5.2 Silicone compound 1 10 20 30 10 10 Silicone compound 2 10 Silicone compound 3 10 Silicone compound 4 10 Inorganic particles (volume %) 78 78 78 78 78 78 78 78 78 76.5 76.5 76.5 Residue rate (mass %) 2 3.6 10 2.5 15 3 2 25 60 1 2 1
[0154] [Table 2]
[0155]
[0156] The details of the materials described in Tables 1 and 2 are as follows.
[0157] Epoxy resin 1: NC-3000 (trade name, Nippon Kayaku Co., Ltd., aralkyl type epoxy resin with epoxy equivalent of 265 g / eq to 285 g / eq and softening point of 53°C to 63°C)
[0158] Epoxy resin 2: EPPN-501HY (trade name, Nippon Kayaku Co., Ltd., triphenylmethane type epoxy resin with epoxy equivalent of 163 g / eq to 175 g / eq and softening point of 57°C to 63°C)
[0159] Epoxy resin 3: N-500P (trade name, DIC Corporation, cresol novolac type epoxy resin with epoxy equivalent of 190 g / eq to 210 g / eq and softening point of 65°C to 70°C)
[0160] Hardener 1: MEHC-7851SS (trade name, Meiwa Chemical Co., Ltd., biphenylene aralkyl type phenol resin with hydroxyl equivalent of 205 g / eq, softening point of 60°C to 70°C)
[0161] Hardener 2: HP-850N (trade name, Resonac Co., Ltd., phenol novolac resin with hydroxyl equivalent of 103 g / eq, softening point of 81°C to 85°C)
[0162] Hardener 3: MEH7500-3S (trade name, Meiwa Chemical Co., Ltd., triphenylmethane type phenol resin with hydroxyl equivalent of 103 g / eq, softening point 50°C to 60°C)
[0163] Inorganic particles 1: a dispersion of spherical silica particles having a maximum particle size of 5 μm or less, a volume average particle size of 1.5 μm, and a specific surface area of 3.0 m2 / g to 4.0 m2 / g as determined by the BET method (dispersion medium: methyl isobutyl ketone, inorganic particle content: 70% by mass)
[0164] Inorganic particles 2: a dispersion of spherical silica particles having a maximum particle size of 5 μm or less, a volume average particle size of 0.3 μm, and a specific surface area of 9.0 m2 / g to 11.0 m2 / g as determined by the BET method (dispersion medium: methyl isobutyl ketone, inorganic particle content: 60% by mass)
[0165] Silicone compound 1: SIM-768E (trade name, Momentive, a silicone compound containing a polyoxyalkylene structure and an epoxy group in the side chain, epoxy equivalent 7300 g / eq, viscosity 3000 mPa·s)
[0166] Silicone compound 2: BY-16-876 (trade name, Dow Toray Co., Ltd., a silicone compound containing a polyoxyalkylene structure and an epoxy group in the side chain, epoxy equivalent 2200 g / eq to 3400 g / eq, viscosity 2500 mPa·s)
[0167] Silicone compound 3: KF-1005 (trade name, Shin-Etsu Chemical Co., Ltd., a silicone compound containing a polyoxyalkylene structure and an aralkyl group in the side chain, epoxy equivalent 250 g / eq, viscosity 2500 mm 2 / s)
[0168] Silicone compound 4: X-22-163C (trade name, Shin-Etsu Chemical Co., Ltd., a silicone compound with epoxy modified at both ends, epoxy equivalent 2700 g / eq, viscosity 120 mm 2 / s)
[0169] Coupling agent: KBM-573 (trade name, Shin-Etsu Chemical Co., Ltd., N-phenyl-3-aminopropyltrimethoxysilane)
[0170] Hardening accelerator: Phosphorus hardening accelerator
[0171] Release agent: montanic acid ester
[0172] Colorant: Carbon black
[0173] As shown in Table 2, it can be seen that the resin composition of the embodiment using the silicone compound containing an oxyalkylene structure as a raw material has a smaller residue rate than the resin composition of Comparative Example 1 not using a silicone compound or Comparative Example 2 using a silicone compound not containing an oxyalkylene structure as a raw material. From the above results, it can be seen that the resin composition of the present disclosure has excellent dispersibility of inorganic particles even if the particle size of the inorganic particles is small.
[0174] The entire contents of the disclosure of Japanese Patent Application No. 2022-196516 are incorporated into this specification by reference.
[0175] All documents, patent applications, and technical specifications described in this specification are cited and incorporated into this specification to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.
Claims
1. A resin composition comprising: a resin component, inorganic particles, and a compound containing an oxyalkylene structure, wherein the maximum particle size of the inorganic particles is 5 μm or less.
2. The resin composition according to claim 1, wherein The resin component includes epoxy resin.
3. The resin composition according to claim 1, wherein The compound containing an oxyalkylene structure includes a silicone compound.
4. The resin composition according to claim 1, which is used as a sealing material for electronic component devices. 5 . An electronic component device comprising an element sealed with the resin composition according to claim 1 .
